2002
DOI: 10.4049/jimmunol.168.5.2154
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of T Cell Epitopes to APC by Use of MHC Class II-Specific Troybodies

Abstract: A major objective in vaccine development is the design of reagents that give strong, specific T cell responses. We have constructed a series of rAb with specificity for MHC class II (I-E). Each has one of four different class II-restricted T cell epitopes genetically introduced into the first C domain of the H chain. These four epitopes are: 91–101 λ2315, which is presented by I-Ed; 110–120 hemagglutinin (I-Ed); 323–339 OVA (I-Ad); and 46–61 hen egg lysozyme (I-Ak). We denote such APC-specific, epitope-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 52 publications
4
35
0
Order By: Relevance
“…T cells in draining lymph nodes of reconstituted BALB/c mice [25]. Consistent with this, we here show that i.v.…”
Section: Injection Of Mhc Class Ii-specific Troybodies Into K2supporting
confidence: 91%
See 1 more Smart Citation
“…T cells in draining lymph nodes of reconstituted BALB/c mice [25]. Consistent with this, we here show that i.v.…”
Section: Injection Of Mhc Class Ii-specific Troybodies Into K2supporting
confidence: 91%
“…Troybodies have proven highly efficient, compared to synthetic peptides, at eliciting T cell responses in vitro and in vivo [23][24][25]. By constructing Troybodies that target thymic APC for efficient delivery of self-T cell epitopes, thymocytes with damaging selfspecificities could possibly be more efficiently deleted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have established that Ab must be internalized and processed before Ab-derived peptides can be presented [4][5][6]17]. Indeed, we demonstrate that T cell activation was abolished if the APC were treated with leupeptin or brefeldin A prior to incubation with CCR1-specific mAb.…”
Section: Discussionmentioning
confidence: 50%
“…The latter strategy has the advantage that it maintains Ig structure and in vivo stability (K. W. Schjetne, unpublished). Ab with T cell epitopes introduced into loops in their C-region can be equipped with V-regions specific for APC [17,27] and have been termed Troybodies. Based on the present results, Troybodies with cloned chemokine receptorspecific V-regions and with T cell epitopes in their C-regions could be a promising strategy for vaccination purposes.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is vaccination, the efficiency of which can be enhanced by optimizing Ag delivery to DCs. This can be done by using Abs specific for DC-expressed molecules as in vivo Ag carriers; using such an approach, a lowered requirement for Ag dose in stimulating immune responses in mice has been observed after targeting a variety of molecules, including MHC class II, CD11c, CD205, CD80/86, F4/80-like receptor (FIRE), CIRE, and the undefined Ag recognized by the mAb 33D1 (1)(2)(3)(4)(5)(6)(7)(8)(9). In addition, in vitro studies have shown that Abs specific for the mannose receptor or DC-SIGN can effectively deliver Ag to human DCs, indicating that this strategy will also be applicable to human vaccination (10,11).…”
mentioning
confidence: 99%